Anti-diabetic Activity of Roots of Ventilago calyculata Tul. in Alloxan Induced Diabetic Rats - Balakrishnan, N.; Singh, Bheem (Asian Journal of Chemistry, 2012)
The purpose of this study was to investigate the antidiabetic potential of the aqueous extracts of roots of Ventilago calyculata Tul. (VCAE) and ethanol extracts of roots of Ventilago calyculata Tul. (VCEE) in the alloxan included diabetic rats. Both extracts of Ventilago calyculata produced a significant antidiabetic activity at dose levels 200 and 400 mg/kg, body weight. Concurrent histological studies of the pancreas of these animals showed comparable regeneration by VCAE and VCEE, which were earlier, necrosed by alloxan.